Interplay between JAK/STAT pathway and non-coding RNAs in different cancers - Ammad Ahmad Farooqi; Abay M. Shepetov; Venera Rakhmetova; Zharilkassimov Ruslan; Aigul Almabayeva; Saniya Saussakova; Kaini Baigonova; Kainish Baimaganbetova; Kalmakhanov Sundetgali; Gulnara Kapanova (Non-coding RNA Research)
Progress in the identification of core multi-protein modules within JAK/STAT pathway has enabled researchers to develop a better understanding of the linchpin role of deregulated signaling cascade in carcinogenesis and metastasis. More excitingly, complex interplay between JAK/STAT pathway and non-coding RNAs has been shown to reprogramme the outcome of signaling cascade and modulate immunological responses within tumor microenvironment. Wealth of information has comprehensively illustrated that most of this complexity regulates the re-shaping of the immunological responses. Increasingly sophisticated mechanistic insights have illuminated fundamental role of STAT-signaling in polarization of macrophages to M2 phenotype that promotes disease aggressiveness. Overall, JAK/STAT signaling drives different stages of cancer ranging from cancer metastasis to the reshaping of the tumor microenvironment. JAK/STAT signaling has also been found to play role in the regulation of infiltration and activity of natural killer cells and CD4/CD8 cells by PD-L1/PD-1 signaling. In this review, we have attempted to set spotlight on regulation of JAK/STAT pathway by microRNAs, long non-coding RNAs and circular RNAs in primary tumors and metastasizing tumors. Therefore, existing knowledge gaps need to be addressed to propel this fledgling field of research to the forefront and bring lncRNAs and circRNAs to the frontline of clinical practice. Leveraging the growing momentum will enable interdisciplinary researchers to gain transition from segmented view to a fairly detailed conceptual continuum.